Penanaman Nilai-Nilai Pancasila melalui Pembelajaran Life Skill di Masa Pandemi Covid-19 - Nur Rochmah Erinawati (Ideguru: Jurnal Karya Ilmiah Guru, 2022)
Education is one of the factors that have an important role in improving the quality of life of a nation. The nation's quality of life can be improved through reforms in education, especially in the systematic paradigm, namely by applying life skills learning. This study aims to find out how to instill Pancasila values ​​through life skills learning during the Covid-19 pandemic. This research is a best practice. The study used a sample of class X BDP students at SMKN 1 Samigaluh Kulon Progo. Data collection techniques were carried out by using questionnaires and observing students' life skill activities. Data analysis technique using descriptive analysis is conducted by accumulating information obtained from observations and questionnaire results, after students carry out life skills learning activities. The results showed that life skills learning could increase the inculcation of Pancasila values ​​in class X BDP students of SMK Negeri 1 Samigaluh Kulon Progo. It is indicated by the percentage of students who cooperate and help each other by 97.2%, sharing by 97.2% and being harmonious with friends and people around them by 86.1%. These Pancasila values ​​are reflected in the gotong royong attitude carried out by students during the Covid-19 pandemic, by helping people who are self-quarantining through the provision of basic necessities. The students' mutual cooperation attitude can be seen from the indicators of the students' willingness to cooperate and help each other, share and establish relationships with friends and the people around them harmoniously.